Reduction of the multidimensional d’Alembert equation to two-dimensional equations - Barannyk, A. F.; Barannik, L. F.; Fushchich, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We give a classification of the maximal subalgebras of rank n - 1 for the extended Poincare algebra AP (1.n), which is realized on the set of solutions of the d’Alembeit equation u + λ u^k = 0. These subalgebras are used for constructing the anzatses reducing this equation to differential equations with two invariant variables.